Identification and functional characterization of cardiac pacemaker cells in zebrafish. - Federico Tessadori; Jan Hendrik van Weerd; Silja B Burkhard; Arie O Verkerk; Emma de Pater; Bastiaan J Boukens; Aryan Vink; Vincent M Christoffels; Jeroen Bakkers (PLoS ONE)
In the mammalian heart a conduction system of nodes and conducting cells generates and transduces the electrical signals evoking myocardial contractions. Specialized pacemaker cells initiating and controlling cardiac contraction rhythmicity are localized in an anatomically identifiable structure of myocardial origin, the sinus node. We previously showed that in mammalian embryos sinus node cells originate from cardiac progenitors expressing the transcription factors T-box transcription factor 3 (Tbx3) and Islet-1 (Isl1). Although cardiac development and function are strikingly conserved amongst animal classes, in lower vertebrates neither structural nor molecular distinguishable components of a conduction system have been identified, questioning its evolutionary origin. Here we show that zebrafish embryos lacking the LIM/homeodomain-containing transcription factor Isl1 display heart rate defects related to pacemaker dysfunction. Moreover, 3D reconstructions of gene expression patterns in the embryonic and adult zebrafish heart led us to uncover a previously unidentified, Isl1-positive and Tbx2b-positive region in the myocardium at the junction of the sinus venosus and atrium. Through their long interconnecting cellular protrusions the identified Isl1-positive cells form a ring-shaped structure. In vivo labeling of the Isl1-positive cells by transgenic technology allowed their isolation and electrophysiological characterization, revealing their unique pacemaker activity. In conclusion we demonstrate that Isl1-expressing cells, organized as a ring-shaped structure around the venous pole, hold the pacemaker function in the adult zebrafish heart. We have thereby identified an evolutionary conserved, structural and molecular distinguishable component of the cardiac conduction system in a lower vertebrate.